Information Society Development in the Customs Union Countries: Legal Framework - Radomir Viktorovich Bolgov (North-West institute of management of the Russian Presidential Academy of National Economy and Public Administration, 2018)
The authors selected comparative analysis to study Information society development covering the Customs Union countries, where integration is rapidly developing (Belarus, Kazakhstan and Russian Federation). The authors have developed a set of parameters for comparing the laws on Information society. The comparison was performed on the priorities as well as terms, goals, and bodies in charge of information society development. The similarities and differences in Information Society legislation of these countries were highlighted. Analysis of implementation of the legislation is based on the comparison of countries positions in global rankings developed by international organizations, as well as open results of intra-governmental audit, and media publications analysis.